Smart Church: IoT Architecture for Prayer Discipline, Togetherness, and Data Security - Gurning, Lisdawati (Cattleya Darmaya Fortuna, 2025)
This research designs and evaluates an edge-centric, local-first IoT-based Smart Church architecture that supports three pillars: prayer discipline, togetherness, and data security/privacy. The method used is mixed-methods engineering + field evaluation with a stepped-wedge design in two church communities for 8 weeks. The system layer includes devices (occupancy, prayer intention buttons, NFC/QR), an edge gateway with store-and-forward (MQTT/CoAP), an event-driven service platform (RBAC/ABAC), and a congregational application/servant dashboard. Technical indicators (p95 latency, uptime, message loss), security/privacy (incidents, time-to-patch, consent opt-in), and socio-spiritual (per capita prayer check-ins, cell group participation, Likert-type perception of togetherness) are measured periodically; qualitative data from interviews/FGDs are analyzed thematically and integrated through a joint display. Pilot results demonstrated consistent technical improvements (decreased p95 latency and message loss, increased uptime), improved prayer discipline (increased weekly check-ins) and togetherness (higher cell participation and togetherness scores), and strengthened security/privacy (fewer incidents, faster time-to-patch, and increased opt-in consent). Qualitative findings confirmed that privacy-conscious ethical nudging and data flow transparency build congregational trust without forcing compliance. Practical implications include the adoption of an edge + store-and-forward pattern with p95 latency/uptime-based SLOs, RBAC/ABAC integration according to church roles, and periodic patching and configuration audit cycles. Limitations of the study include the short time horizon and limited community scale; further research is recommended with longer durations, cluster randomization, and exploration of privacy-preserving analytics (e.g., differential/federated) to ensure that spiritual-communal benefits remain aligned with the dignity and confidentiality of the congregation.